The impact of recycling abandoned sites on sustainable development - Abd Almonim , Sondos (Journal of Planner and Development, 2021)
In today's cities, it is easy to see large numbers of vacant lands and unused abandoned sites in downtown areas that are not only ugly but also potentially becoming fertile ground for criminal activities that endanger residents and visitors and contribute to the further degradation of neighborhoods,can provide reuse of spaces Neglected opportunities to reshape the appearance of the city and to improve the city center for its users that the presence of many neglected sites, whether they were abandoned buildings or sites for destroyed buildings in Mosul after the war on ISIS and with large areas amid the urban fabric led to the emergence of the research problem is (lack of urban planning to reactivate abandoned sites within the city’s fabric)so that the research goal (adopting a new job for neglected spaces until they become attractive and beneficial and thus increase economic growth in the city center) within the research hypothesis (recycling of abandoned sites depends on the characteristics of those sites) From here, the research went to study the classification and characteristics of abandoned sites and spaces and how they relate to sustainable development.